Assessment of the effectiveness of selected blowing agents in the injection molding of thermoplastic materials - Palutkiewicz, P.; Garbacz, T. (Polimery, 2021)
The aim of this work was to evaluate the effectiveness of chemical blowing by using various blowing agents in the process of high density polyethylene (HDPE) injection molding. Six types of blowing agents were used, including four endothermic and two exothermic ones. The parts were molded either with or without holding pressure. The mass, density, dimensional stability, surface state and structure of molded parts were assessed. Also, the processability of the mixture of plasticized HDPE with blowing agent was evaluated on the basis of its flow into the injection mold with spiral cavity. The growth of pores and mass flow rate (MFR) of the plastic-blowing agent mixture were investigated using a self-designed test stand.